Acute onset of bulbar amyotrophic lateral sclerosis after flu – look at the differential diagnosis: A case report. Issue 7 (July 2018) - Portaro, Simona; Brizzi, Teresa; Naro, Antonino; Conti Nibali, Valeria; Morabito, Rosa; Bramanti, Alessia; Calabrò, Rocco Salvatore
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder affecting upper and lower motor neurones. It can be either familial (fALS) or sporadic (sALS). ALS is characterized by muscle weakness and atrophy that can involve the limbs and trunk (i.e. the spinal form of the disease) or speech and swallowing (i.e. the bulbar form). The aetiology of sALS remains unclear although a gene–environment interaction has been proposed as a concomitant trigger for the neurodegenerative process together with viral infections, smoking, heavy metals and pesticide exposure. Herein, we report the case of a 67-year-old woman who experienced an acute onset of bulbar ALS with an atypical clinical course that was probably triggered by a bout of influenza.